Cost-effectiveness analysis of case management for optimized antithrombotic treatment in German general practices compared to usual care: Results from the PICANT trial - Lisa-Rebekka Ulrich-Müssig; Juliana Petersen; Karola Mergenthal; Andrea Berghold; Gudrun Pregartner; Rolf Holle; Andrea Siebenhofer-Kroitzsch (Health Economics Review, 2019)
Background: By performing case management, general practitioners and health care assistants can provide additional benefits to their chronically ill patients. However, the economic effects of such case management interventions often remain unclear although how to manage the burden of chronic disease is a key question for policy-makers. This analysis aimed to compare the cost-effectiveness of 24 months of primary care case management for patients with a long-term indication for oral anticoagulation therapy with usual care. Methods: This analysis is part of the cluster-randomized controlled Primary Care Management for Optimized Antithrombotic Treatment (PICANT) trial. A sample of 680 patients with German statutory health insurance was initially considered for the cost analysis (92% of all participants at baseline). Costs included all disease-related direct health care costs from the payer's perspective (German statutory health insurers) plus case management costs for the intervention group. A-Quality Adjusted Life Year (QALY) measurement (EQ-5D-3 L instrument) was used to evaluate utility, and incremental cost-effectiveness ratio (ICER) to assess cost-effectiveness. Mean differences were calculated and displayed with 95%-confidence intervals (CI) from non-parametric bootstrapping (1000 replicates). Results: N = 505 patients (505/680, 74%) were included in the cost analysis (complete case analysis with a followup after 12 and 24 months as well as information on cost and QALY). After two years, the mean difference of direct health care costs per patient ( exteuro115, 95% CI [- 201; 406]) and QALYs (0.03, 95% CI [- 0.04; 0.11]) in the two groups was small and not significant. The costs of case management in the intervention group caused mean total costs per patient in this group to rise significantly (mean difference exteuro503, 95% CI [188; 794]). The ICER was exteuro16,767 per QALY. Regardless of the willingness of insurers to pay per QALY, the probability of the intervention being costeffective never rose above 70%. Conclusions: A primary care case management for patients with a long-term indication for oral anticoagulation therapy improved QALYs compared to usual care, but was more costly. However, the results may help professionals and policy-makers allocate scarce health care resources in such a way that the overall quality of care is improved at moderate costs, particularly for chronically ill patients. Trial registration: Current Controlled Trials ISRCTN41847489.
Keywords: 330; Anticoagulants [MeSH]; Chronic disease [MeSH]; Cost-effectiveness analysis; Primary health care [MeSH]; Case management [MeSH]; Health services research [MeSH]